Moderasi Islam Pada Tafsir Sunda Ayat Suci Lenyepaneun Karya Mohammad Emon Hasim - Irfan Setia Permana; Siti Juju Juariah; Ari Prayoga (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
Al-Quran and al-Hadith are the main sources of reference in Islam, Islam is a religion blessed by Allah SWT which was conveyed by Rasulullah Saw to Muslims, in al-Quran it is mentioned if Muslims are the best ummah, the chosen ummah and the just ummah. . In the reality of the life of Muslims, it is the opposite, for example the emergence of radical groups and liberal groups, the debate on the matter of Furu 'iyah. The purpose of this research is to examine 2 issues, namely: How the interpretation of Moh. Emon Hasim on the concept of Moderation in the scope of Islam according to Moh. Emoh Hasim and the interpretation of Moh. Emon Hasim on the verses of wasathiyah. This research uses the method of maudhu'i (thematic), library research (Library Research) is qualitative descriptive. Data search technique is by way of documentation (photos) of books related to this research. The results show that there are two sources of data that form the basis of this study; first, the primary data source by using Tafsir Ayat Suci Lenyepaneun by Moh. Emon Hasim son of al-Qur’an al-Karim. Second, secondary data sources can be from works such as, books, scientific works or journals that have relevance to this research. The conclusion is sourced from Moh. Emon Hasim in the interpretation of the holy verses Lenyepaneun wasathan ummah which is the ummah that can uphold justice, balance and tolerant behavior towards human beings, as described in Surat al-Baqarah verse 143, Surat al-Maidah verse 89, Surat al-Adiyat verse 5, Surat al-Qalam verse 28 and Surat al-Baqarah verse 238. describes the principles of moderation in the scope of Islam and the behavior of moderate Muslims in accordance with the Qur'an, which is described as 3 terms, term adl in Surat al - Baqarah verse 282, surat al- Baqarah verse 124, and al- Hadid verse 25, the term tawazun in Surat al- Infithar verse 6- 7, Surat ar- Rahman verse 7 and al- Mulk verse 3, the term tasamuh is in Surat al - Imran verse 64, Surat al-Imran verse 159 and Surat al-Kafirun verses 1- 6.